Tourism and SME development: Performance of tourism SMEs in coastal tourist destinations in southern Sri Lanka - N. P. Ravindra Deyshappriya; A. M. D. B. Nawarathna (Asian Development Bank Institute (ADBI), 2020)
The current study investigated whether tourism-related small and medium-sized enterprises (SMEs) perform better than non-tourism-related SMEs in the four main coastal tourist destinations - Hikkaduwa, Galle, Mirissa, and Tangalle - in the Southern Province of Sri Lanka. The authors used the survey-based quantitative research methodology to accomplish the objectives of the research. More specifically, they surveyed 200 SMEs, of which 117 were related to tourism and 83 were not, to collect the data required for the study. As the survey findings highlight, the majority of SME owners are male, irrespective of the SME type. Moreover, the survey recognized six main business types of non-tourism SMEs: agriculture, farming, and dairy; arts and crafts; apparel and bags; auto parts and maintenance; household items; and cement and metalwork. Conversely, it recognized businesses such as hotels and homestays; spas and ayurveda; cafes, food, and beverages; traveling and guiding; surfing and diving; and souvenirs and handicrafts as common business types of tourism-related SMEs. Moreover, the average profit of tourism-related SMEs is considerably higher than both the average profit of non-tourism SMEs and the average profit of the entire sample of SMEs. However, the education level of tourism-related SME owners is slightly lower than that of non-tourism-related SME owners. The econometric analysis confirmed that tourism-related SMEs have higher profit and higher productivity than non-tourism-related SMEs. The estimated models also confirmed that factors such as firms' capital assets, number of workers, sales revenue, level of human capital, and size positively affect SMEs' profit and productivity. Hence, the current study strongly recommends motivating people who are interested in creating a tourism-related SME in the studied areas by providing the necessary training and initial capital for them to start their business.
Keywords: O27; L83; M30; Q01; 330; small and medium-sized enterprises; ocean tourism; tourism-related SMEs; coastal tourism destinations